T-cut slotted quartz tube-atom trap strategy for the on-line preconcentration of thallium in well water samples - Bombom, Miray; Zaman, Buse Tugba; Bozyigit, Gamze Dalgic; Saylan, Meltem; Bayraktar, Ahsen; Arvas, Busra; Yolacan, Cigdem; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2023)
In this study, an on-line preconcentration system was developed for the quantitative determination of thallium in well water samples using hydrogen-assisted T-cut slotted quartz tube atom trapping (HA-T-SQT-AT) coupled to flame atomic absorption spectrometry (FAAS). The method is based on trapping the thallium atoms on the inner surface of the T-SQT for a short period using sample aspiration and lean flame conditions. Then, hydrogen gas as a reducing agent was released instantly to free the trapped analyte atoms, resulting in a sharp and narrow signal. The system analytical performance was enhanced by performing comprehensive optimization of several factors. The linear range and LOD/LOQ values of the optimized method were found to be 7.5---200 ng/mL and 2.6/8.7 ng/mL, respectively. Accuracy/practicability of the presented method were verified using well water samples, and the percent recoveries calculated using the external calibration approach were all above 80%.
Keywords: Thallium; Flame atomic absorption spectrometry; Atom trap; T-shaped slotted quartz tube; Well water; CLOUD POINT EXTRACTION; ABSORPTION-SPECTROMETRY; ICP-OES; GENERATION; INDIUM; Engineering; Instruments & Instrumentation